Neurocognitive abilities in individuals with Down syndrome-a narrative review - Jafri, Sidra Kaleem; Harman, Karen Elizabeth (The Turkish Journal of Pediatrics, 2020)
Down syndrome (DS), or trisomy 21, is the most common genetic syndrome associated with intellectual disability. Despite the variability in expression, there is a distinct developmental phenotype characterized by deficits in learning/memory, executive functions, and language skills accompanying the psychomotor delay. The severity of intellectual impairment has the dominant effect on functioning, other influences such as parental and societal attitudes, supports available and social opportunities also play a role in the attainment of skills.
Keywords: Down syndrome; cognition; learning